Oral health and nutrition: addressing disparities in socioeconomically disadvantaged older adults in rural China - Qiufeng Gao; Xintong Wang; Yuxin Jiang; Wenhua Chen; Kaixuan Gao; Yaojiang Shi (BMC Public Health)
Abstract Background Inequalities in oral health and nutrition present substantial challenges for vulnerable older adults. Although poor oral health is known to increase the risk of inadequate dietary quality and compromised nutritional status, limited evidence exists on this relationship among socioeconomically disadvantaged older adults in rural areas—a particularly vulnerable population. This study investigates the association between oral health, dietary quality and nutritional status among socioeconomically disadvantaged older adults in rural China. Methods A cross-sectional study was conducted among 310 socioeconomically disadvantaged older adults aged 60 or above in rural Shaanxi province, northwest China. Oral health was assessed using indicators of oral problems measured by the 5-item Oral Health Impact Profile (OHIP-5) and the number of missing teeth. Dietary quality was evaluated through the Simplified Healthy Eating Index (SHEI) and dietary patterns, while nutritional status was assessed using the Short-Form Mini Nutritional Assessment (MNA-SF). Multiple linear regression examined associations between oral health, adherence to a healthy diet and nutritional status, while quantile regression analyzed its relationship with dietary patterns. Results Among participants, an average of 14.08 teeth were missing, increasing to 17.30 when considering number of missing teeth not replaced with dentures. The mean OHIP-5 score was 5.78. The average SHEI score was 14.70, and the mean MNA-SF score was 11.57. Regression analyses consistently showed a negative association between poor oral health and both adherence to a healthy diet—including reduced intake of the “vegetable and meat” dietary pattern—and nutritional status. Heterogeneity analysis found no significant variations across care arrangements and family poverty status. Conclusions This study highlights the critical relationship between oral health, dietary quality and nutritional status among socioeconomically disadvantaged older adults in rural China. The findings underscore the need for targeted interventions to improve oral health, dietary intake and nutritional well-being in aging populations with disadvantaged and rural settings.